Significance of Cyclin D1 Polymorphisms in Patients with Head and Neck Cancer. Issue 1 (January 2013) - Sabir, Maimoona; Baig, Ruqia Mehmood; Mahjabeen, Ishrat; Kayani, Mahmood Akhtar
Cyclin D1 plays a key role in cell cycle control, particularly in the transition from G1 to S phase, regulated by cyclin-dependent kinases. The objective of the present study was to screen the cyclin D1 gene (CCND1) for polymorphisms in patients with head and neck cancer (HNC). Genomic DNA was isolated from blood samples of 380 HNC patients and 350 controls. In a hospital-based case-control study using the PCR-SSCP technique we found 3 novel germline mutations: g3578C>A, g3475G>C and g3383delA. The commonly reported guanine to adenine polymorphisms in exon 4 g7656G>A (rs9344) and g10861C>A (rs7177) in 3′UTR of CCND1 were also observed. The calculated frequencies of the g7656G>A (rs9344) polymorphism in GG, GA and AA genotypes were 27.3%, 38.6%, and 33.9% in HNC cases, and 44.2%, 29.4%, and 26.2% in normal healthy controls, respectively. Adjusted by age (in years), sex and smoking status, multivariate logistic regression analysis showed that the AA and GA genotypes were associated with a significantly increased risk (OR 1.34, 95% CI 1.03-1.64, p=0.028) for HNC. The CCND1 AA genotype variant was associated with an increased risk in individuals who were <40 years old (OR 1.45, 95% CI 1.02-2.08, p=0.04). In conclusion, it is suggested that the CCND1 G/A polymorphism is associated with the early onset of HNC and may contribute to HNC susceptibility in a Pakistani population.